Facile preparation of a rubidium ion-imprinted polymer by bulk polymerization for highly efficient separation of rubidium ions from aqueous solution. (14th May 2021) - Zhou, Zhiyong; Hu, Yulei; Wang, Zhuo; Zhang, Hewei; Zhang, Bing; Ren, Zhongqi
Abstract : A novel rubidium ion-imprinted polymer was prepared by bulk polymerization for selective adsorption of Rb(i ). Abstract : A novel rubidium ion-imprinted polymer (Rb + -IIP) was successfully prepared by bulk polymerization with the Rb + ion as the template ion, methacrylic acid (MAA) as the functional monomer, 18-crown-6 (18C6) ether as the selective ligand, ethylene glycol dimethacrylate (EGDMA) as the cross-linking agent and 2, 2′-azobisisobutyronitrile (AIBN) as the initiator. The Rb + -IIPs showed efficient adsorption performance for Rb + ions due to the macrocyclic effect and the intermolecular hydrogen bond formed between 18C6 and MAA. Several types of characterization were used for confirming the successful formation and surface structure of imprinted polymers. The effects of preparation and adsorption conditions on the adsorption performance of Rb + -IIPs were also systematically investigated. The Rb + -IIPs reached the adsorption equilibrium within 6 min, demonstrating fast adsorption kinetics. The adsorption data of Rb + -IIPs agreed well with the pseudo-second-order kinetic and Langmuir isotherm models. The maximum adsorption capacity of Rb + -IIPs was 213.08 mg g −1 at pH 9.8. Rb + -IIPs showed good selectivity for Rb + ions in the presence of Li +, Na + and K + ions. Moreover, the 8 times repeated adsorption–desorption results demonstrated the excellent reusability of Rb + -IIPs.